2017
DOI: 10.1177/1471301217725185
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of group reminiscence therapy for people living with dementia in a day care centers in Taiwan

Abstract: Objective To explore as a pilot study the effects of group reminiscence therapy upon depression of people living with dementia within dementia-specific day care centers. Method A unique pre-test-post-test, quasi-experimental design counterbalanced with a qualitative grounded theory video analysis of facial expression and behavior was used to measure the effects of group reminiscence therapy. The study recruited 21 participants in total from two dementia-specific day care centers. Results The findings highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In assessing the effect of laughter therapy versus group reminiscence therapy on sleep quality of elderly in nursing homes of India, the results indicated that both interventions were significantly effective but laughter therapy had more impact on sleep quality in elderly (33). Chang and Chien (2018) assessed the impact of group reminiscence intervention on depression in older adults with dementia using the Cornell Scale for Depression in Dementia (CSDD). They evaluated sleep disorders as one of the subsets of this scale and they did not find any highlighted decrease in sleep disorders of these people (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In assessing the effect of laughter therapy versus group reminiscence therapy on sleep quality of elderly in nursing homes of India, the results indicated that both interventions were significantly effective but laughter therapy had more impact on sleep quality in elderly (33). Chang and Chien (2018) assessed the impact of group reminiscence intervention on depression in older adults with dementia using the Cornell Scale for Depression in Dementia (CSDD). They evaluated sleep disorders as one of the subsets of this scale and they did not find any highlighted decrease in sleep disorders of these people (32).…”
Section: Discussionmentioning
confidence: 99%
“…Chang and Chien (2018) assessed the impact of group reminiscence intervention on depression in older adults with dementia using the Cornell Scale for Depression in Dementia (CSDD). They evaluated sleep disorders as one of the subsets of this scale and they did not find any highlighted decrease in sleep disorders of these people (32). Furthermore, in assessment of sleep disorders in older patients with Alzheimer's disease, researchers did not find a significant change due to reminiscence intervention (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group MM may affect apathetic mood by increasing engagement. While previous studies have not examined the effects of delivery format on mood, group reminiscence therapy was found to positively affect QoL [19–23].…”
Section: Discussionmentioning
confidence: 99%
“…Another emerging finding from the literature is a potential differential effect of reminiscence delivery format [8,9]. Group reminiscence therapy positively affects QoL in some participants [19–23], whereas personalized approach may be essential for other participants [17,24]. However, no studies have examined the effects of delivery format for gaming‐based reminiscence.…”
Section: Introductionmentioning
confidence: 99%